(untitled) (Agricultural Engineering, 2017)
A comparative analysis of milk production in Poland and Belarus was carried out. The basic tendencies of modern development of the dairy industry and offered upcoming trends of innovative modernization of milk production processes were analyzed. On the basis of the analysis of trends in the global production of milk and new scientific knowledge on the biosynthesis of milk, a conceptual approach to the design of equipment for machine milking, is provided, considered the relationship of technical and physiological parameters.